Legal Protection for Victims of Crimes of Sexual Violence Viewed from a Victimological Perspective - Mardhatillah, Dini; Ramdan Al Musthafa, Muhammad (Gayaku Publisher, 2022)
Victims of sexual violence need to get legal protection, both preventively and repressively. This study aims to analyze efforts to restore the rights of victims of sexual violence and their legal protection. This research is a normative legal research using statutory approach and consepal approach. The data obtained were analyzed with descriptive analysis. The results of this study conclude that the criminal procedural law in Indonesia is not optimal in paying attention to the rights of victims of criminal acts, but besides that there is a study of victimology that focuses on victims of crime including how legal protection efforts are made. Preventive protection in Indonesia has been quite good with the introduction of regulations as a legal basis for victims of sexual violence crimes who, with their various remedies, access justice and remedy through protection for the Witness and Victim Protection Agency (LPSK). In addition, they can also obtain compensation in the form of money for losses suffered as well as assistance with medical and psychological and psychosocial costs. However, education facilities for child victims have not been covered by the regulation, even though victims of sexual violence who drop out of school need to violate their right to education according to their needs. In addition, in developing repressive protection, law enforcers related to cases of sexual violence, such as investigators and public prosecutors, must actively provide information related to efforts to protect and compensate for losses that can be accessed by victims.